IMPLEMENTASI PEMBELAJARAN IPA MATERI SISTEM REPRODUKSI PADA MANUSIA DENGAN BERBASIS SENI SAINS DAN CERITA BERGILIR - A Fauzanul Hakim (Universitas Jember, 2021)
This learning innovation activity aims to improve the strategy and quality of natural science learning, thereby increasing student learning activities, being able to express opinions and asking questions, absorb 21st century skills, namely collaborative, communicative, creative and critical thinking, have high literacy and art improve student learning results. The subjects of this research were students of class IXE SMPN 1 Torjun Sampang Madura, to taling 28 people. Data collection techniques are using observation sheets and test scores for learning outcomes, namely pre test and post test. Using statistical analysis and quantitative presented descriptively. The results showed that there had been an increase in the average student learning outcomes from 65,53 to 79,07 after learning based on art and science and taking turns story was carried out. Student learning activities are also getting better with an average of 2,06 (good enough) to 2,74 (good). While teacher activities are obtained and average of 2,30 (good) to 3,10 (very good). Thus learning activities based on the art of science and taking turns story can be used as a strategy in learning natural science subject.